The Effect of Overconfidence on Trading Activity and Investment Returns in Simulated Stock Markets - Aprilina Susandini; R. A. Norromadani Yuniati; M. Boy Singgih Gitayuda; Moh. Zaki Kurniawan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study is motivated by increasing market volatility and the growing complexity of investment decision-making, where investor behavior does not always reflect rational considerations, highlighting the importance of psychological biases, particularly overconfidence. The objective of this study is to examine the effect of overconfidence levels on stock trading activity and investment returns, as well as to analyze differences in investor responses to market information in the form of good news and bad news. This study employs an experimental design involving 68 undergraduate students, who are classified into high- and low-overconfidence groups based on calibration test results. Trading activity is measured using trading frequency and volume, while investment performance is assessed through returns. Data are analyzed using independent samples t-tests and paired samples t-tests. The findings indicate that investors with high overconfidence exhibit significantly higher trading frequency and volume compared to those with low overconfidence under both good and bad news conditions. Moreover, highly overconfident investors tend to be less responsive to differences in market information, whereas low-overconfidence investors demonstrate more adaptive behavior. The results also reveal that overconfidence negatively affects investment returns. In conclusion, overconfidence significantly influences trading behavior and investment performance, contributing to market inefficiency.